More impact by combining old and new tools - Ilboudo, Jean-Pierre (Technical Centre for Agricultural and Rural Cooperation, 2005)
Jean-Pierre Ilboudo of the UN Food and Agriculture Organisation explains why food and nutrition deserve better coverage through all media.